PENEREPAN METODE DEBAT AKTIF UNTUK MENINGKATKAN HASIL BELAJAR PKN KELAS IV SDN 016 KUSAU MAKMUR KECAMATAN TAPUNG HULU - Saputra, Hengky; Witri, Gustimal; Kurniaman, Otang (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The study design was a classroom action research (CAR). Research was conducted in two cycles of four meetings and two replications of material daily. Background of the problem in this study is the low student learning outcomes fourth grade in public primary schools 016 kusau makmur with an average value of 66.17% of 34 students reached the KKM beelom as many as 22 people (64,70%). KKM while reaching only 12 people (35,30%). formulation of the problem in this research “is the research debate active method can improve learning outcomes of students on the subjects of Civics fourth grade in public primary schools 016 Kusau Makmur ?”. The purpose of this research to improve the learning outcomes of students in learning civics by applying an active debate. The experiment was conducted in the second semester in March 2016 of the school year 2015/2016 subjects were fourth grade in public primary schools 016 Kusau Makmur by the number of students 34 people, consisting of 13 boys and 21 girls. Data collection instrument in this study is the observation sheet and the teacher and the student achievement test. Based on these results it can be concluded that the application of active learning methods debates can improve learning outcomes of students of fourth grade in primary school 016 Kusau Makmur Tapung Hulu district Kampar regency. Key Words: Active debate methods, learning outcomes